Computer Vision in Esophageal Cancer: A Literature Review - Domingues, Ines (2019)
Esophageal cancer is a disease with a high prevalence that can be evaluated by a variety of imaging modalities, including endoscopy, computed tomography, and positron emission tomography. Computer-aided techniques could provide a valuable help in the analysis of these images, decreasing the medical work ow time and human errors. The goal of this paper is to review the existing literature on the application of computer vision techniques in the domain of esophageal cancer. After an initial phase where a set of keywords was chosen, the selected terms were used to retrieve papers from four well-known databases: Web of Science, Scopus, PubMed, and Springer. The results were scanned by merging identical entries, and eliminating the out of scope works, resulting in 47 selected papers. These were organized according to the image modality. Major results were then summarized and compared, and main shortcomings were identi ed. It could be concluded that, even though the scienti c community has already paid attention to the esophageal cancer problem, there are still several open issues. Two major ndings of this review are the nonexistence of works on MRI data and the under-exploration of recent techniques using deep learning strategies, showing the need for further investigation.